Hypothermic machine perfusion can safely prolong cold ischemia time in deceased donor kidney transplantation. A retrospective analysis on postoperative morbidity and graft function. Issue 5 (8th January 2021) - Adani, Gian Luigi; Pravisani, Riccardo; Tulissi, Patrizia; Isola, Miriam; Calini, Giacomo; Terrosu, Giovanni; Boscutti, Giuliano; Avital, Itzhak; Ekser, Burcin; Baccarani, Umberto
Abstract: In deceased donor kidney transplantation (KT), a prolonged cold ischemia time (CIT) is a negative prognostic factor for KT outcome, and the efficacy of hypothermic machine perfusion (HMP) in prolonging CIT without any additional hazard is highly debated. We conducted a retrospective study on a cohort of 154 single graft deceased donor KTs, in which a delayed HMP, after a preliminary period of static cold storage (SCS), was used to prolong CIT for logistic reasons. Primary outcomes were postoperative complications as well as 1 year graft survival and function. 73 cases (47.4%) were managed with HMP and planned KT, while 81 (52.6%) with SCS and urgent KT. The median CIT in HMP group and SCS group was 29 hour:57 minutes [27‐31 hour:45 minutes] and 11 hour:25 minutes [9‐14 hour:30 minutes], respectively ( P  < .001). The period of SCS in the HMP group was significantly shorter than in the SCS group (10 vs. 11 hour:25 minutes, P  = .02) as well as the prevalence of expanded criteria donors was significantly higher (43.8% vs. 18.5%, P  < .01). After propensity score matching for these two baseline characteristics, the HMP and SCS groups showed comparable outcomes in terms of delayed graft function, vascular, and urologic complications, infections, and episodes of graft rejection. At 1 year follow‐up, serum creatinine levels were comparable between the groups. Therefore, the use of HMP to prolong the CIT and convert KT into a planned procedure seemed to have an adequate safety profile, with outcomes comparable to KT managed as an urgent procedure and a CIT nearly three time shorter. Abstract : The use of hypothermic machine perfusion to prolong cold ischemia time (CIT) and convert kidney transplantation (KT) into a planned procedure seems to have an adequate safety profile, with outcomes comparable to KTs managed as an urgent procedure and a CIT nearly three time shorter.